FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI PUSKESMAS SIDOMULYO PEKANBARU TAHUN 2016 - Sarlis, Nelfi; Ivanna, Cindy Netta (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Based on data in 2010 show 4 million children under five are malnourished in Indonesia, 700 thousand of them suffering from severe malnutrition. The purpose of this study was to determine the factorsassociated with the nutritional status of children in the Puskesmas Sidomulyo Pekanbaru in 2016. Type of quantitative research with analyticcorrelations and in cross sectional study design.The place is in the puskesmas research Sidomulyo Pekanbaru, population that will be taken are mothers who have children numbering 280 people in the period on August to October 2015. The total sample of 165 people. The sampling technique using consecutive sampling. Analysis processing techniques with univariate and bivariate. The result of the bivariate analysis of the relationship between knowledge of the nutritional status of children, in the can P-value= 0.000, a=0,05. ThenHo is rejected and Ha received means that there is a significant relationship between knowledge of the nutritional status of children, there is a relationship between the opinion of the nutritional status of children, in the P-value=0.000, a= 0,05. Then Ho is rejected and Ha received means that there is a significant relationship between the opinion of the nutritional status of children, while the relationship between Exclusive breastfeeding with infant nutritional status, P-value= 0.709, a= 0,05. Then Ho is accepted and Ha rejected meaning there is no significant relationship between breastfeeding with infant nutritional status in Puskesmas Sidomulyo Pekanbaru 2016. Berdasarkan data tahun 2010 memperlihatkan 4 juta balita di Indonesia kekurangan gizi, 700 ribu diantaranyamengalami gizi buruk. Tujuan penelitian ini adalah untuk mengetahuifaktor-faktor yang berhubungan dengan status gizi balita di Puskesmas Sidomulyo Pekanbaru Tahun 2016.Jenis penelitian kuantitatif dengan analitik kolerasi dan desain penelitian secara crosssectional. Tempat penelitian yaitu di Puskesmas Sidomulyo Pekanbaru. Populasi yang akan diambil adalah seluruh ibu yang memiliki balita berjumlah 280 orang periode bulan Agustus hingga Oktober 2015. Jumlah sample sebanyak 165 orang. Denganteknikpengambilansampelmenggunakan consecutive sampling. Teknik pengolahan dengan analisis univariat dan bivariat. Hasil analisis bivariatterdapat hubunganantara pengetahuan dengan status gizi balita, didapat P-value = 0.000,α=0,05. Maka disimpulkan terdapat hubungan yang bermakna antara pengetahuan dengan status gizi balita, terdapat hubungan antara pendapatan dengan status gizi balita, didapat P-value = 0.000, α=0,05. Maka disimpulkanterdapat hubungan yang bermakna antara pendapatan dengan status gizi balita, sedangkan hubungan antara ASI Ekslusif dengan status gizi balita, P-value = 0.709, α=0,05. Maka disimpulkan tidak terdapat hubungan yang bermakna antara ASI Ekslusif dengan status gizi balita di wilayah kerja Puskesmas Sidomulyo Pekanbaru Tahun 2016.